Design of Gear Transmission Contact Ratio Detection System - Rongxian Wang; Danwen Zhang; Tailing Chen; Jianhang He; Biao Wu (Jixie chuandong)
The wear and deformation of gear profile will change the contact ratio，which will affect the continuity and bearing capacity of gear transmission. In order to detect the change of contact ratio in time，the detection system of gear transmission is designed. The detection system consists of gear transmission detection device and data analysis software. The industrial camera is used to capture the moving image of gear meshing，and image analysis is carried out based on the digital speckle correlation method，and the relevant parameters and contact ratio of gear mechanism are measured. The detection system can check the contact ratio of different types of gear transmission，with fast detection speed，high accuracy and convenient use. It provides a technical reference for gear design，processing and detection.